1995
DOI: 10.1111/j.1558-5646.1995.tb02332.x
|View full text |Cite
|
Sign up to set email alerts
|

Penguins, Petrels, and Parsimony: Does Cladistic Analysis of Behavior Reflect Seabird Phylogeny?

Abstract: Whether or not behavior accurately reflects evolutionary relationships (phylogeny) has been hotly debated by ethologists and comparative psychologists. Previous studies attempting to resolve this question have generally lacked a quantitative, phylogenetic approach. In this study we used behavior and life-history (BLH) information (72 characters) to generate phylogenetic trees for 18 seabird species (albatrosses, petrels, and penguins). We compared these trees with trees obtained from isozyme electrophoretic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 78 publications
1
43
1
Order By: Relevance
“…The use of behavioral traits as phylogenetic characters has received increasing support in recent years (16)(17)(18)(19)(20)(21). Although nest structure and placement are species specific behavioral traits, our study suggests that these traits are unlikely to be phylogenetically informative in swiftlets.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The use of behavioral traits as phylogenetic characters has received increasing support in recent years (16)(17)(18)(19)(20)(21). Although nest structure and placement are species specific behavioral traits, our study suggests that these traits are unlikely to be phylogenetically informative in swiftlets.…”
Section: Discussionmentioning
confidence: 81%
“…However, recent studies (17)(18)(19)(20)(21) show that behavioral characters contain useful phylogenetic information. Hence, the reliance of swiftlet taxonomists on these kinds of characters is not unreasonable a priori.…”
mentioning
confidence: 99%
“…However, this assumes that gains and losses are equally likely. It has often been suggested that complex characters are more readily lost than gained (e.g., Paterson et al 1995). Our favored interpretation of galaxiid evolution rests on the contention that diadromy, once lost, is unlikely to be regained.…”
Section: Diversification: Repeated Loss Of Diadromy or Freshwatermentioning
confidence: 92%
“…Nucleotide characters are especially useful where phenotypic homologies are not clear (Raff et al 1994;Aguinaldo et al 1997;McHugh 1997) or few shared derived phenotypic states can be observed (Avise et al 1994). Molecular and phenotypic data often give results that are congruent or at least not strongly conflicting (Eernisse et al 1992;Rumbak et al 1994;Lafay et al 1995;Paterson et al 1995;Reid et al 1996), and combining these character types may allow the inclusion of fossil or other taxa for which molecular data are unavailable (e.g., Wiens 1998). The total evidence approach has sometimes been cautiously extended to include phenotypic characters from marine invertebrate gametes, embryos, and larvae (Reid 1990;Rouse & Fitzhugh 1994;Reid et al 1996;Wray 1996).…”
mentioning
confidence: 99%